A systematic assessment of the quality of systematic reviews/meta‐analyses in radiofrequency ablation versus hepatic resection for small hepatocellular carcinoma. Issue 2 (May 2014) - Wang, Yingqiang; Luo, Qianqian; Li, Youping; Deng, Shaolin; Li, Xianglian; Wei, Shiyou
Abstract Objectives The systematic reviews (SRs) of radiofrequency ablation (RFA) versus hepatic resection (HR) for early hepatocellular carcinoma (HCC) are increasing with varies qualities. The aim of this study is to evaluate quality and their impacts on outcomes of these studies. Methods We searched six databases and five official websites to find the SRs of RFA versus HR for early HCC. The Overview Quality Assessment Questionnaire (OQAQ), the Cochrane Collaboration's tool, and modified MINORS score were applied to assess their quality for SRs, randomized (RCTs) and nonrandomized controlled trials (NRCTs), respectively. Results Nineteen SRs were included. The results showed that the overall quality was poor, with a mean OQAQ score of 3.3 and 95%CI 2.6 to 4.1, only five (26.3%) SRs were good quality, six (31.6%) misused the statistical models, and three of them changed outcome direction after modification. Five SRs taken retrospective studies as RCT. In addition, a total of 39 primary studies referenced by these 19 SRs were included. The results showed that 3 RCTs were leveled grade B, and 35 NRCTs were of moderate quality, with an estimated mean MINORS score of 15.0 and 95%CI 14.6 to 15.4. Conclusions The overall quality of SRs comparing the effects between RFA and HR for early HCC was poor. There was high heterogeneity and low evidence level. Physicians should take caution when applying the results from these studies to their clinical practice.